Significance of Intercellular adhesion molecule-1 Lys496Glu gene polimorphism on plasma redox status regulation in laryngeal carcinoma - Yanar, Karolin; Atayik, Mehmet Can; Horozoğlu, Cem; Demirkol, Şeyda; Simsek, Bahadir; Verim, Aysegul; Küçükhüseyin, Özlem; Aydın, Seval; Yaylım, İlhan; Çakatay, Ufuk (Journal of cancer research and therapeutics, 2023)
ABSTRACT Background: Intercellular adhesion molecule-1 (ICAM-1) is a surface glycoprotein important for tumor invasion and angiogenesis. The present research is conducted to investigate whether specific gene polymorphism of ICAM-1 K469E (rs5498) and plasma redox status could be associated with laryngeal cancer (LC) development. Since there is no clear evidence which investigates the relationship between ICAM-1 polymorphism and ROS-mediated plasma protein oxidation in LC, our study is the first significant contribution for investigating the relationship. Methods: The study covered patients with primary LC and their age-matched healthy control subjects. Evaluation of ICAM-1 K469E (rs5498) gene polymorphism was performed by polymerase chain reaction-restriction fragment length polymorphism. Plasma redox status was assessed with spectrophotometric methods. Results: In the current paper, we found that LC patients with GG genotype had a decreasing trend for the plasma oxidative damage biomarker levels when compared with all allele genotypes (AA and AG). Conclusion: We concluded that G allele of the ICAM-1 K469E gene plays a significant role in the optimal regulation of plasma redox homeostasis in patients with LC.